Podocarpus elatus R.Br. Leaf Extracts are Ineffective Inhibitors of the Growth of a Panel of Bacterial Pathogens - Mpala, Lindiwe; Chikowe, Getmore; Cock, Ian (Pharmacognosy Communications)
Introduction: Closely related plant species often share similar secondary metabolites and bioactivities and are therefore good targets for bioactivity testing when one or more species within a genus are known to possess therapeutic properties. The genus Podocarpus has a long history of medicinal usage in many areas of the world. Many species are known to have therapeutic properties, several species of which have well established antibacterial bioactivities. Materials and Methods: The ability of P. elatus leaf extracts to inhibit the growth of a panel of bacterial pathogens was investigated by disc diffusion assay. Toxicity was examined using the Artemia franciscana nauplii bioassay. Results: The P. elatus methanolic and aqueous extracts were ineffective at inhibiting the growth of gram-positive and gram-negative panels of bacteria and were nontoxic in the Artemia lethality assay following 24 hr exposure. Conclusion: Despite its reported therapeutic uses against other diseases and its close taxonomic relationship with several bioactive Podocarpus spp. with antibacterial activity, P. elatus leaf extracts were ineffective bacterial growth inhibitors. However, these extracts may have other therapeutic properties and testing against protozoa, fungi, virus and tumour cells is required.
Keywords: Podocarpaceae; Illawarra plum; Brown plum; Plum pine; Traditional medicine; Medicinal plants; Toxicity.